RELIGION: POLITICAL FACTOR IN THE MUSLIM REGIONS OF RUSSIA - DUBININA, Natalia (CENTRAL ASIA AND THE CAUCASUS, 2017)
Today, the religious factor has become a part of the political processes and as such a catalyst of stabilization/destabilization of political space. This means that to ensure social and state security, we should identify the mechanisms and technologies that add political dimensions to religion. For several decades, politically biased religious organizations and their destabilizing influence remained limited to certain regions of the world. Today, radical Islamic movements threaten not only individual states and regions, but also the world community as a whole. Islamic extremism is no longer a local problem—it has become a transnational phenomenon. In the last few years, Islamic radicalism has spread far and wide to certain regions of the CIS (I have in mind Central Asia) and Russia (the Northern Caucasus, the Volga Area, and Siberia). For a long time, the North Caucasian peoples have been taught to think that the national and religious factors were inseparable; they were united by their religion, while the confession that was taking shape on the national soil imbibed local customs, traditions, and rites. Similar processes are unfolding among the Islamic peoples of Siberia and the Volga Area. This adds urgency to the subject discussed and makes it much more interesting.